Unique solvability and exponential stability of differential hemivariational inequalities. Issue 14 (25th October 2020) - Li, Xiuwen; Liu, Zhenhai; Sofonea, Mircea
ABSTRACT: In this paper, we study a differential hemivariational inequality (DHVI, for short) in the framework of reflexive Banach spaces. Our aim is three fold. The first one is to investigate the existence and the uniqueness of mild solution, by applying a general fixed-point principle. The second one is to study its exponential stability, by employing the formula for the variation of parameters and inequality techniques. Finally, the third aim is to illustrate an application of our abstract results in the study of an initial and boundary value problem which describes the contact of an elastic rod with an obstacle.